COMPETITIVE METHODS FOR CHALLENGE BETWEEN SHIPPING LINES IN CASE OF BUILDING AND PRFORMING SEA SHIPPING CONTAINER LINES - E. Fadeev; T. Bogdanova; S. Goncharenko (Вестник университета, 2016)
There was competition between world alliances for many years. In this work we found historical economic aspects of competition of international container shipping lines and possibilities to enter the world container market for new entities.